Lycium ruthenicum water extract preserves retinal ganglion cells in chronic ocular hypertension mouse models - Liu, Jinfeng; Zhou, Lina; Wu, Xueping; Chen, Zihang; Zheng, Xiaofei; Wang, Huajun; So, Kwok Fai; Ma, Lan; Wang, Jiantao; Chiu, Kin (Frontiers in Pharmacology, 2024)
Lycium ruthenicum Murray (LR), known as "black goji berry" or "black wolfberry", is widely utilized in chinese herbal medicine. LR fruit showed its antioxidant and/or anti-inflammation activity in treating cardiac injury, experimental colitis, nonalcoholic fatty liver disease, fatigue, and aging. Glaucoma is the leading cause of irreversible blindness. Besides elevated intraocular pressure (IOP), oxidative stress and neuroinflammation were recognized to contribute to the pathogenesis of glaucoma.This study investigated the treatment effects of LR water extract (LRE) on retinal ganglion cells (RGCs) threatened by sustained IOP elevation in a laser-induced chronic ocular hypertension (COH) mouse model and the DBA/2J mouse strain. The antioxidation and anti-inflammation effects of LRE were further tested in the H2O2challenged immortalized microglial (IMG) cell line in vitro. LRE oral feeding (2 g/kg) preserved the function of RGCs and promoted their survival in both models mimicking glaucoma. LRE decreased 8-hydroxyguanosine (oxidative stress marker) expression in the retina. LRE reduced the number of Iba-1+ microglia in the retina of COH mice, but not in the DBA/2J mice. At the mRNA level, LRE reversed the COH induced HO-1 and SOD-2 overexpressions in the retina of COH mice. Further in vitro study demonstrated that LRE pretreatment to IMG cells could significantly reduce H2O2 induced oxidative stress through up-regulation of GPX-4, Prdx-5, HO-1 and SOD-2. Our work demonstrated that daily oral intake of LRE can be used as a preventative/treatment agent to protect RGCs under high IOP stress probably through reducing oxidative stress and inhibiting microglial activation in the retina.